AN IMPROVEMENT OF NEW TEST METHOD FOR DETERMINATION OF VEGETABLE OIL QUALITY BASED ON ELECTROOPTICS PARAMETER - Firdausi, K Sofjan; Triyana, Kuwat; Susan, Ade Ika (BERKALA FISIKA, 2012)
An improvement of measurement for determination of frying oil quality has been conducted based on electrooptics parameter. The samples were several palm oils, coconuts oil, arefine olive oil, and a corn oil. The measured electrooptics parameter was the change of light polarizationθ through the samples within an external electric field, which leads to the increase oftransmitted lightζ, obtained by tabulating θ via Malus’ Law. The electric field was produced by high DC voltage power supply 0-10 kV on two parallel plates in a separated distance of circa 1 cm. The sources of light were red diode laser 5 mW (λ=650 nm), green diode laser 5 mW (λ=532 nm), He-Ne laser 1 mW (λ=633 nm), and a 100W-ligth bulb. For palm oils, the average value Δζwas approximately between 3×10-4 and 8×10-4. For coconuts oil and corn oil, Δζ was in the rangevalue of palm oils. However for refine olive oilΔζ was the smallest, out of the range and indicated minimum amount of free radicals. The electrooptics parameter here could classify various types offrying oils, distinguish between fresh oils and used oils, and also distinguish between edible oilsand expired oils.  This method could be an alternative quality test of frying oils. It conductedwithout additional treatments, relative simple, and quite accurate.Keywords: electrooptics, frying oil, polarization, transmitted light